2017
DOI: 10.3349/ymj.2017.58.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Clear Cell Carcinoma Sub-Typing by ARID1A Expression

Abstract: PurposeLoss of AT-rich DNA-interacting domain 1A (ARID1A) has been identified as a driving mutation of ovarian clear cell carcinoma (O-CCC), a triple-negative ovarian cancer that is intermediary between serous and endometrioid subtypes, in regards to molecular and clinical behaviors. However, about half of O-CCCs still express BAF250a, the protein encoded by ARID1A. Herein, we aimed to identify signatures of ARID1A-positive O-CCC in comparison with its ARID1A-negative counterpart.Materials and MethodsSeventy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Since somatic mutations of ARID1A loss have been frequently identified in OCCC, classified OCCC based on ARID1A expression status also helped to distinguish distinct subtype of OCCC. ARID1A-positive tumors were more likely to be histologically of high grades, ERβ-positive, HNF1β-negative and E-cadherin-negative than ARID1A-negative tumors, but without difference of age, parity, tumor stage and cancer-specific survival 39 . However, BAF250a encoded by ARID1A is a member of the SWI/SNF complex, aggressive behaviors and poor prognosis were observed in the OCCC losing one or multiple SWI/SNF complex subunits 40 .…”
Section: Molecular Classification Of Occcmentioning
confidence: 89%
“…Since somatic mutations of ARID1A loss have been frequently identified in OCCC, classified OCCC based on ARID1A expression status also helped to distinguish distinct subtype of OCCC. ARID1A-positive tumors were more likely to be histologically of high grades, ERβ-positive, HNF1β-negative and E-cadherin-negative than ARID1A-negative tumors, but without difference of age, parity, tumor stage and cancer-specific survival 39 . However, BAF250a encoded by ARID1A is a member of the SWI/SNF complex, aggressive behaviors and poor prognosis were observed in the OCCC losing one or multiple SWI/SNF complex subunits 40 .…”
Section: Molecular Classification Of Occcmentioning
confidence: 89%
“…The findings of the relatively limited number of survival analyses conducted to investigate the prognostic value of the ARID1A gene in the outcome of cancer treatment appear to be controversial as well. Actually, relevant studies have reported adverse, beneficial or absolutely no effect of protein loss on the biological behaviour and metastaticity of tumours, the outcome of chemotherapy, the recurrence of cancer, the PFS and the OS of cancer patients, thus clarifying that the abnormal expression of ARID1A affects the prognosis in different ways, mainly depending on the type, stage and grade of the tumour (107,110,117,136).…”
Section: Discussionmentioning
confidence: 99%
“…Four studies on the effects of the mutant gene on the prognosis of ovarian cancer found no significant differences in tumour progression, clinical status and OS between ARID1A protein-positive and -negative patients (127,128,130,136). By contrast, Ayhan et al associated the loss of ARID1A expression with cancer stages I and II and Itamochi et al with a significant reduction of OS of patients at these specific cancer stages (103,119).…”
Section: Summary Of the Findings Of Previous Studies Regarding Arid1a In Cancermentioning
confidence: 99%
“…Increasing interest has been focused on determining whether the suppression of ARID1A is associated with poor prognosis in patients with OCCC. A study by Previous studies reported that ARID1A deletion was related to worse survival in OCCC [ 12 18 ]. In other studies, no significant difference in survival was found between the absence and presence of ARID1A [ 19 20 ].…”
Section: Introductionmentioning
confidence: 99%